DESERTIFICATION IN NORTHERN MOROCCO DUE TO EFFECTS OF CLIMATE CHANGE ON GROUNDWATER RECHARGE - Dijck, Simone J. E. Van; Laouina, Abdellah; Carvalho, Anabela V.; Antari, Mostafa; Rocha, Alfredo; Borrego, Carlos; Coen, J. (Desertification in the Mediterranean Region a Security Issue, 2006)
Groundwater resources in Morocco are expected to shrink in the next decades due to an increasing withdrawal for rural and urban development, and a decreasing internal recharge by precipitation under the influence of climate change. The objective of this work is to analyse the recharge of groundwater systems in a region with traditional agriculture and current transformations in northern Morocco (Sehoul region) in response to future climate change and land degradation. Models were used to simulate climate change and effects on surface runoff and groundwater recharge. The climate models indicated increases in temperature and decreases in precipitation in all seasons in 2050 compared to 1990, and an increasing variability of autumn precipitation. Because most cultivated fields are freshly ploughed and sown in autumn, this will increase the risk of desertification due to declining groundwater recharge and increased surface runoff and erosion. This is confirmed by the results of the event-based surface runoff simulation for the 2050 climate. Surface runoff is mainly produced in ancient grazing fields and fallow fields. In view of the current transformation of collective grazing fields into cultivated land, problems with loss of rainfall in surface runoff and soil erosion could be mitigated by 1. early tillage of cultivated fields along the slope contour, followed by leveling, 2. locating cultivated fields downslope of grazing fields to enable the capturing of diffuse surface runoff coming from the grazing fields, and 3. leaving fallow fields untilled and covered with crop remnants. The groundwater modeling results indicate a decrease of the annual groundwater recharge by rainfall of 40-68% from the climate centered in 1990 to the climate centered in 2050. As a result, groundwater levels are predicted to fall up till 2005, but the results are unreliable due to model errors. However, the decreases in precipitation, infiltration and groundwater recharge predicted in this study may be expected to add to the observed trend of groundwater level decrease in the study area, and to continuing desertification.
The following values have no corresponding Zotero field: periodical: Desertification in the Mediterranean Region a Security Issue
Keywords: climate change; Grazing; groundwater; land degradation (voyant); Morocco; Precipitation; surface runoff

DESERTIFICATION IN NORTHERN MOROCCO DUE TO EFFECTS OF CLIMATE CHANGE ON GROUNDWATER RECHARGE (Desertification in the Mediterranean Region a Security Issue, 2006)
Groundwater resources in Morocco are expected to shrink in the next decades due to an increasing withdrawal for rural and urban development, and a decreasing internal recharge by precipitation under the influence of climate change. The objective of this work is to analyse the recharge of groundwater systems in a region with traditional agriculture and current transformations in northern Morocco (Sehoul region) in response to future climate change and land degradation. Models were used to simulate climate change and effects on surface runoff and groundwater recharge. The climate models indicated increases in temperature and decreases in precipitation in all seasons in 2050 compared to 1990, and an increasing variability of autumn precipitation. Because most cultivated fields are freshly ploughed and sown in autumn, this will increase the risk of desertification due to declining groundwater recharge and increased surface runoff and erosion. This is confirmed by the results of the event-based surface runoff simulation for the 2050 climate. Surface runoff is mainly produced in ancient grazing fields and fallow fields. In view of the current transformation of collective grazing fields into cultivated land, problems with loss of rainfall in surface runoff and soil erosion could be mitigated by 1. early tillage of cultivated fields along the slope contour, followed by leveling, 2. locating cultivated fields downslope of grazing fields to enable the capturing of diffuse surface runoff coming from the grazing fields, and 3. leaving fallow fields untilled and covered with crop remnants. The groundwater modeling results indicate a decrease of the annual groundwater recharge by rainfall of 40-68% from the climate centered in 1990 to the climate centered in 2050. As a result, groundwater levels are predicted to fall up till 2005, but the results are unreliable due to model errors. However, the decreases in precipitation, infiltration and groundwater recharge predicted in this study may be expected to add to the observed trend of groundwater level decrease in the study area, and to continuing desertification.